PENGARUH TIME BUDGET PRESSURE, AKUNTABILITAS DAN OBJEKTIVITAS TERHADAP KUALITAS AUDIT (Studi Empiris pada Kantor Akuntan Publik Di Sumbar, Riau dan Kepri) - Indah, Afrina; Andreas, Andreas; Elfi, Ilham (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
The study aims to learn about (1) the effects of time's budget pressure (2) the effects of accountability (3) the effect of objectivity on the quality of the audit. This research was done in a public accountant's office. The data used on this study is primary data with a questionnaire as an instrument. The method used for selection of samples is sampling (sample retrieval is based on the availability of elements and easier to obtain them). The number of samples in this study is 75 respondents of 25 KAP. Hypothetical testing was done using a double version of regency analysis using a statistic test used with SPSS 17. The results of this study indicate that time budget pressure has a significant impact on the quality of the audit at a rate of 0.001 significance, accountability has a significant impact on the quality of the audit at a depth of 0.001, and effectiveness has a significant effect on the quality of the audit at a degree of 0.001 in the public accounting office.Keywords: Audit Qualit, Time Budget Pressure, Accountability, Objectivity